Bioenergy and Social Economic Transformation in Rural Area (Case Studies: Talau Village and Tanjung Beringin Village, Pelalawan Regency, Riau Province) - Astriani Sudaryanti, Diyane; Fauzi, Akhmad; Dharmawan, Arya Hadi; Kumala Putri, Eka Intan (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTElectrical energy becomes a priority for Indonesia because there are still many areas that have not been electrified especially in rural areas. Bioenergy as one of the energy fulfillment solutions for new renewable energy source becomes one of the focus for the development of new renewable energy in Indonesia. Oil palm, as an indigenous resource in some parts of Indonesia, can be used as a bioenergy source. Utilization of bioenergy especially for the electricity needs (biopower) can be sourced from the waste palm oil Palm Oil Mill Effluent (POME). The purpose of this research is to analyze how the opportunity of POME converted to biopower can meet the electricity needs of the rural community and want to know how biopower from POME could be able to grow the economy in rural society. The research used the descriptive qualitative-quantitative method and in-depth interview. The results show that bioenergy can present an incentive to foster the dynamic movement of the rural development. By using indigenous resources in each region as a bioenergy feedstock, the government’s spirit to build Indonesia’s electric sovereignty finds a bright spot. In addition, to provide economic benefits through savings and additional people’s income, this activity is socially able to reduce conflicts due to pollution, to foster the moving forward spirit especially for the next generation, and to suppress negative externalities that were previously as the environmental responsibility.Keywords: Bioenergy, Economic, Electricity, Oil Palm, Palm Oil Mill Effluent (POME)ABSTRAKEnergi listrik menjadi prioritas bagi Indonesia karena masih terdapat begitu banyak wilayah yang belum tersentuh jaringan listrik khususnya di wilayah pedesaan. Bioenergi sebagai salah satu solusi pemenuhan kebutuhan energi listrik terbarukan menjadi salah satu fokus dalam kegiatan pembangunan sumberdaya energi terbarukan di Indonesia. Kelapa sawit, adalah salah satu sumberdaya alam yang terdapat di Indonesia, dapat digunakan sebagai sumber bioenergi. Penggunaan bioenergi terutama pada sektor kelistrikan (biopower) dapat diperoleh dengan menggunakan limbah hasil pemrosesan kelapa sawit yang sering dikenal dengan istilah Palm Oil Mill Effluent (POME). Tujuan dari penelitian ini adalah untuk menganalisis bagaima peluang konversi POME menjadi biopower agar dapat memenuhi kebutuhan listrik masyarakat pedesaan dan untuk mengetahui bagaimana bioenergi yang berasal dari POME dapat membantu pertumbuhan perekonomian di pedesaan. Penelitian ini menggunakan metode kualitatif deskriptif - kuantitatif serta wawancara mendalam. Hasil penelitian menunjukkan bahwa bioenergi dapat berkontribusi dalam upaya percepatan pembangunan wilayah pedesaan. Dengan menggunakan berbagai sumberdaya alam dari masing-masing daerah sebagai sumber bioenergi, semangat pemerintah untuk memenuhi kebutuhan kelistrikan di wilayah Indonesia menemui titik terang.Kata Kunci: Bioenergi, ekonomi, pasokan listrik, kelapa sawit, Palm Oil Mill Effluent (POME)